Second Language Learning: Cultural Adaptation Processes in International Graduate Students in U.S. Universities - Herold, Mariella Espinoza (Journal of International Students, 2012)
The impact of globalization, the rapid technical advancements, and the access to educational opportunities have attracted large numbers of bright international students to study in the United States. Graduate and undergraduate international students as well as foreign-born faculty are now visible in American higher education institutions